Improving the professional competence of future music teachers on the basis of uzbek status - Bobokulov Kahramon Sadullayevichi (Genius Journals, 2023)
Based on the modern requirements of pedagogical family educational institutions, the formation and development of professional competence of future music teachers on the basis of Uzbek national music, on the basis of the current methodology of the formation and development of highly qualified music teachers on the basis of advanced foreign experiences, innovative educational technologies teacher training.
Keywords: pedagogue; spiritual; educational